(untitled) (Cadernos de Sociomuseologia, 2020)
The main scope of this article is to reflect on the representations and functions of memory in old age, symbols and expressions that involve this concept, as well as its "usefulness" and incumbency in this time of life. This is an initial analysis, whose stimulus arose from interviews conducted for an academic research about the construction of memory in a neighborhood of the West zone of the city of Rio de Janeiro. We analyze here the cases of his Durval, his Salviano and Silvan Guedes, three of the interviewees for the aforementioned research, residents of the neighborhood of Sepetiba, located in the West zone of the city, which one day possessed notoriety and expression and currently is degraded and forgotten. Keywords: Representations; Memory; Old age; Sepetiba.